ATZagenda worldwide - SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: .)
With (3z(BATZagenda(3y (BSpringer Vieweg has expanded its family of ATZ products with a new Premium Edition. For the first time, a comprehensive approach will be used to examine and assess the latest developments in all areas concerning the automobile from various perspectives. There are currently many challenges and new business areas alike. And the best way for companies to approach these challenges is with new ideas, courage, and an intensive exchange of information.s
Keywords: Engineering; Engineering, general